მიქაელ არამიანცი და საქართველო - ავდალიანი, ემილ (My University, 2018)
The incorporation of Georgia into the Russian Empire in the beginning of the 19th century, quite surprisingly, played as a catalyzer for the development of entrepreneurial activity in late 19th-early 20th centuries Georgia. There were several important factors favoring this development in Georgia: stable internal as well as external political situation around the country; geographic proximity of the Ottoman and Persian Empires; Russian Empire’s economic interests such as growth of trade in order to compete with major European states (France and Great Britan) for the marlets in these two Middle East countries. Thus, the proximity of Georgia to the Ottoman and Persian Empires was reflected in trade growth and other economic activities between the two countries on the one hand and the South Caucausus overall on the other. This development is well reflected in various biographies of Georgian or foreign entrepreneurs working in Georgia. These economic and political developments led to Tbilisi being steadily transformed throughout the 19th century into an entrepreneurial center of the South Caucaus. A look at the map shows that the geographic location too favored the city as it is located right in the center of the entire Caucasus. Moreover, a relatively good condition of transportation roads around Tbilisi also helped the city gain a prominent position in the region. For instance, in Mikael Aramiants’ biography we see how he eventually left Baku to manage his business empire from Tbilisi. Yet another reason for transforming Tbilisi into a hub of political and business activity was the Tsarist administration which chose the city as its capital in the Caucasus. Meagre academic literature as well as newspapers were used to give a full biography of the entrepreneur Mikael Aramiants. His biography is notable as beyond the South Caucasus, his business was also spread in major European and Asian cities. Aramiants’ life shows the economic and administrative centrality of Tbilisi in the region. Indeed, after each success and failure in his business career Aramiants headed to Tbilisi where he eventually settled to manage his business empire. Moreover, research on his life provided here is far more important from a purely academic point of view as until now there have not been any notable works done on this issue neither in Georgian, nor in Russian.
MIKAEL ARAMYANTS AND GEORGIA
https://geohistory.humanities.tsu.ge/ge/procedings/83-shromebi/171-shromebi-14.html
Keywords: მიქაელ არამიანცი; ნავთობი; სავაჭრო გზები